2007
DOI: 10.1016/j.jcrs.2007.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront aberration and its association with intraocular pressure and central corneal thickness in myopic eyes

Abstract: Intraocular pressure was associated with wavefront aberrations in both the cornea and the whole eye, and its association was not limited to symmetrical aberrations but included asymmetric higher-order aberrations as well. In contrast, CCT was very weakly associated with wavefront aberrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…The relatively greater variation in ocular aberration than in corneal aberration infers that there is larger variability in internal aberrations contributed by the crystalline lens and ocular media, although this cohort only consisted of healthy myopic patients seeking refractive surgery. We compared the aberration values in this study with those in studies of Asian eyes and Caucasian eyes [13][14][15][16][17][18][19][20] (Table 2). To ensure the validity of these population comparisons, only studies in which wavefront measurements were obtained using Hartmann-Shack aberrometers were included to avoid wavefront differences linked to measurement technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively greater variation in ocular aberration than in corneal aberration infers that there is larger variability in internal aberrations contributed by the crystalline lens and ocular media, although this cohort only consisted of healthy myopic patients seeking refractive surgery. We compared the aberration values in this study with those in studies of Asian eyes and Caucasian eyes [13][14][15][16][17][18][19][20] (Table 2). To ensure the validity of these population comparisons, only studies in which wavefront measurements were obtained using Hartmann-Shack aberrometers were included to avoid wavefront differences linked to measurement technologies.…”
Section: Discussionmentioning
confidence: 99%
“…From the corneal heights, exported from the ATLAS system, wavefront aberrations for the anterior cornea were calculated using a customized MatLab ray-tracing program [18][19] to derive Zernike aberration terms up to the 7 th order (35 terms). The corneal height data were originally referenced to corneal vertex in the ATLAS system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have also tested a group of young myopes for comparison. Moreover, wavefront aberrations in the anterior corneal surface were examined using a precisely calibrated corneal topography system, 18,19 because the anterior cornea plays an important role in determining wavefront aberrations in the whole eye. 18,[20][21][22][23] …”
Section: Introductionmentioning
confidence: 99%
“…For each corneal measurement, Zernike aberrations up to 7 th order (35 terms) were calculated using a customized MatLab ray-tracing program [8][9] from the height data exported from the ATLAS system. The data of corneal heights within a 4.5 mm corneal central area were calculated, and the Zernike aberrations in the whole eye within a 4.5 mm central pupil area were obtained by reprocessing the WASCA data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, intraocular pressure was recently found to be related to vertical coma. 9 Studies on the effects of reading on corneal aberrations also revealed that the eye lid pressure could change the vertical coma as well as the trefoil. 13 Besides the coma aberration, weak but significant correlations were found for several other Zernike aberrations.…”
Section: Discussionmentioning
confidence: 99%